RANCANG BANGUN SISTEM INTERNET OF THINGS DAN PREDIKSI KADAR AIR MI KERING BERBASIS ARTIFICIAL INTELLIGENCE PADA MESIN DEHIDRATOR UNTUK PENGERINGAN MI SEHAT - Moh Fahri Ferdiansyah; Raden Arief Setyawan; n/a Nurussa’adah (Jurnal Mahasiswa TEUB, 2022)
Mi Sehat is one of the output products of the Mie Serdadu UKM. Different from instant noodles in general, which use preservatives, Mie Sehat owned by Mie Serdadu UKM prioritizes consumer health, so it uses organic ingredients and no preservatives. In order to maintain the quality and taste of noodles, it is necessary to use good and healthy preservation techniques for consumers. One way to keep noodles in good condition for a long time is to dry them. The long drying time and the lack of workers are separate problems for Mie Serdadu UKM. In this study, a remote control and monitoring system based on the internet of things was designed that was equipped with an artificial intelligence system to predict the moisture content of dry noodles in the healthy noodle dehydrator machine owned by the Mie Serdadu UKM. The design process uses Esp8266, Raspberry Pi, and PHP Webserver. The communication protocol used is HTTP. The test is intended to determine the time it takes Esp8266 to send and receive data using the HTTP communication protocol. In the artificial intelligence system, the prediction accuracy between th